EFFECT OF N AND K FERTIGATION SCHEDULES ON YIELD ATTRIBUTES AND YIELD OF SUNFLOWER (Helianthus annus L.) - M. MADHAVI, K. PREETHIKA REDDY, M. UMA DEVI, V. RAMULU and (The Journal of Research, PJTSAU, 2019)
Sunflower ranks third in the area and fourth in production in world. It is cultivated in an area of 18.22 million hectares with an annual production and productivity of 22.03 million tones and 1216 kg ha-1 respectively, in the world (Anonymous, 2015). Sunflower (Helianthus annuus L.) is an important oilseed crop in India. It is cultivated over an area of about 5.2 lakh hectares with a production of 3.35 lakh tonnes and productivity of 643 kg ha-1 (Anonymous, 2015).